Morphological and morphometrical studies of the human foetal lung - Mukhia, Rajeev; Mansur, Dil Islam; Timsina, Sidharth; BK, Taneja (Asian Journal of Medical Sciences, 2019)
Background: Foetal lung is one of the organs of interest for researchers since a long time. Though, detailed study about adult lung is there in the literature but lungs at different stages in foetal period is less available. Aims and Objective: To find out the morphological and morphometrical features of the foetal lung in different gestational weeks. Materials and Methods: After ethical approval the study was carried out on 66 human foetal lungs aged between 16th to 40th gestational weeks in the Department of Anatomy, Manipal College of Medical Sciences. After the dissection of foetuses, the lungs were removed out and the presence of fissures and lobes for both lungs were noted. Weights of both lungs were calibrated by digital weighing machine. Dimensions of foetal lungs were recorded by vernier calliper. All the data were represented as mean then analyzed with MS excel 2007 software and represented graphically. Results: In the normally developing foetuses the dimensions of both lung increases with increase in gestational age with more or less difference between the dimension of right and left lung. There was number of variations seen in the fissures and lobes of the lungs. Conclusion: The fissures and lobes are needed for locating broncho-pulmonary segments hence, knowledge of their position is necessary both anatomically as well as clinically for planning lobectomies and surgical resections.